Dimensi Profetisme Pengembangan Ilmu Sosial dalam Islam Perspektif Kuntowijoyo - Syamsul Arifin (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2014)
In 1980s, the development of Islam in Indonesia was characterized by “intellectual boom” as a great result of success of some Indonesian young Muslim intellectuals who accomplished their study abroad. This phenomenon has been a positive sign for the development of Islam in Indonesia as world’s largest Muslim country. One of the expected contribution of Indonesian Islam is the development of Islamic thought. One of Muslim intellectuals who had tried to respond to this expectation was Kuntowijoyo. Kuntowijoyo had produced many works in various fields, in addition to history which becomes the major of his field studies. One important thought of Kuntowijoyo’s intellectual legacies that should be appreciated and reconstructed is the idea of Prophetic Social Sciences (ISP). This article attempts to reconstruct and elaborate the ISP, which has been initiated by Kuntowijoyo, into Prophetic Sociology. In doing so, the writer refers to Kuntowijoyo’s works and other relevant sources to the issue. Keywords: prophetic social sciences, prophetic sociology.